Measuring the synergy between emotional exhaustion and the behavior political of managers - Al – Ghazali, FadhelRadi; Razaq Alaboody, Ali Abd Al; Ali Balchat, Baqer (Opción, 2019)
The aim of the study is to investigate the synergy between emotional exhaustion and the strategic behavior political of managers to achieve organizational glue via a statistical set of methods, and the importance relative, and the global empirical analysis through the use of Amos version 23. As a result, there is a correlation between the emotional exhaustion and the political behavior of the managers on the organizational glue. In conclusion, there is a high level of focus by the sample in question to encourage its affiliates to express their personal views in all frankness.